Radiomonitoring at “Nurobod Meat and Dairy” Llc in Nurobod District of Samarkand Region - Khakimov B.N.; Mirzaev B.Sh.; Ayupova J.R. (American Journal of Biodiversity, 2026)
This article presents the results of radiometric monitoring conducted at “Nurobod Meat and Dairy” LLC located in the Nurobod district of the Samarkand region. During the study, samples of soil, alfalfa, water bodies, and hay collected from the farm territory were analyzed under laboratory conditions to determine their radiation levels. Based on the obtained results, the radiation background of the area was assessed, and scientific conclusions were drawn to ensure the safety of livestock products.